1997
DOI: 10.1063/1.366079
|View full text |Cite
|
Sign up to set email alerts
|

Raman scattering study of surface barriers in GaAs passivated in alcoholic sulfide solutions

Abstract: Raman scattering has been used to study the variation of surface barriers in GaAs due to sulfur passivation in solutions of ammonium sulfide [(NH4)2S] in different alcohols (ethanol, isopropanol, and tert-butanol). It has been found that the surface barrier height and the depletion layer width decrease considerably with the decrease of the dielectric constant of the passivating solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 9 publications
2
41
0
2
Order By: Relevance
“…Moreover, the treatment with the aqueous sulfide solution has very little effect on surface recombination velocity in n-GaAs(100). These data are in a good agreement with the previous results of photoluminescence and Raman scattering study of n-GaAs(100) passivated with aqueous and alcoholic solutions of ammonium sulfide [27,28]. In particular, it was found that after the treatment of GaAs(100) surface with aqueous sulfide solution the photoluminescence intensity increases, whereas the surface depletion layer width that characterizes the density of the occupied surface states remains unchanged [28].…”
Section: Resultssupporting
confidence: 81%
“…Moreover, the treatment with the aqueous sulfide solution has very little effect on surface recombination velocity in n-GaAs(100). These data are in a good agreement with the previous results of photoluminescence and Raman scattering study of n-GaAs(100) passivated with aqueous and alcoholic solutions of ammonium sulfide [27,28]. In particular, it was found that after the treatment of GaAs(100) surface with aqueous sulfide solution the photoluminescence intensity increases, whereas the surface depletion layer width that characterizes the density of the occupied surface states remains unchanged [28].…”
Section: Resultssupporting
confidence: 81%
“…Spectra were taken in a backscattering geometry allowing both longitudinal (LO) and coupled phonon-plasmon mode scattering to be observed [30]. Raman scattering studies were performed on wafers of n-GaAs(1 0 0) [N D = 1 Â 10 18 cm À3 ] and p-GaAs(1 0 0) [N A = 1 Â 10 18 cm À3 ], which prior to adsorption of HS À ions were etched in HCl for 100 s at room temperature to remove native oxide layer [6,7]. The corresponding surface depletion layer width for these semiconductors were d n0 = 33.6 nm and d p0 = 26.9 nm, respectively, i.e., considerably lower than the penetration depth of laser excitation into GaAs.…”
Section: Methodsmentioning
confidence: 99%
“…the semiconductor surface (surface recombination velocity, depletion layer width) as a function of the dielectric constant and molecular properties of the solvents [5][6][7]. It is well known that the solute-solvent interaction can affect the valence shell of the solvated ion [8], the reaction pathway [9], and the properties of chemical bonds formed in the solution [10].…”
Section: Introductionmentioning
confidence: 99%
“…Surface treatments for III-V compound semiconductor wafers by sulfide compounds were shown to enhance the photoluminescence response and improve the electrical properties by removing the oxygen on the surfaces and reducing the surface trap state densities. [13][14][15][16][17][18] Although this well-known technique has never been employed for direct bonded interfaces, this study shows that the wafers with residual sulfur atoms can be directly bonded without decreasing the bonding strength at the interfaces. In addition, sulfide-passivated interfaces give a significant improvement of the interfacial electrical conductivities and direct bonding of heavily doped p-GaAs and n-InP wafers after sulfide passivation forms a tunnel diode at temperatures as low as 300°C.…”
Section: Introductionmentioning
confidence: 99%